Men and apparitions : a novel - Tillman, Lynne (New York : Soft Skull Press, 2018)
"The time is now, and Ezekiel Hooper Stark is thirty-eight. He's a cultural anthropologist, an ethnographer of family photographs, a wry speculator about images. From childhood, his own family's idiosyncrasies, perversities, and pathologies propel Zeke, until love lost sends him spiraling out of control in Europe. Back in the U.S.A., he finds unexpected solace in the image of a notable nineteenth-century relative, Clover Hooper Adams. Zeke embarks on a project, MEN IN QUOTES, focusing his anthropological lens on his own kind: the "New Man," born under the sign of feminism. All the old models of masculinity are broken. How are you different from your father? Zeke asks his male subjects. What do you expect from women? What does Zeke expect from himself? And what will the reader expect of Zeke--is he a Don Quixote, Holden Caulfield, Underground Man, or Stranger? Kaleidoscopic and encyclopedic, comic, tragic, and philosophical, Men and Apparitions showcases Lynne Tillman not only as a brilliantly original novelist but also as one of our most prominent contemporary thinkers on art, culture, and society."--Provided by publisher.
boek
Keywords: Feminism; Photographs; Masculinity in popular culture; Identity (Psychology)